Nitretação iônica sem efeito de borda :desenvolvimento e avaliação de uma nova técnica - Sousa, Rômulo Ribeiro Magalhães de (2006)
The ionic nitriding process presents some limitations related with the control of the thickness of the layer and its uniformity. Those limitations that happen during the process, are produced due to edge effects, damage caused by arcing arc and hollow cathode, mainly in pieces with complex geometry and under pressures in excess of 1 mbar. A new technique, denominated ASPN (active screen shapes nitriding) it has been used as alternative, for offering many advantages with respect to dc plasma conventional. The developed system presents a configuration in that the samples treated are surrounded by a large metal screen at high voltage cathodic potencials, (varying between 0 and 1200V) and currents up to 1 A. The sample is placed in floting potential or polarized at relatively lower bias voltages by an auxiliary source. As the plasma is not formed directly in the sample surface but in the metal screen, the mentioned effects are eliminated. This mechanism allows investigate ion of the transfer of nitrogen to the substrate. Optical and electronic microscopy are used to exam morphology and structure at the layer. X-ray difration for phase identification and microhardness to evaluate the efficiency of this process with respect to dc conventional nitriding